JSA and HIRADC Analysis of Mold Replacement Process on Inject Stretch Blow Machine - Rahman Soesilo (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
In plastic packaging companies using the Inject stretch blow machine (ISBM) process, changing molds is an activity that has the potential for work accidents. This is based on work activities carried out involving equipment that is quite heavy and has enormous dimensions. The purpose of this research is to find out the hazard factors of work accidents that occur and provide the development of solutions to avoid work accidents. This study uses the Job Safety Analysis (JSA) method and the Hazard Identification Risk Assessment and Determining Control (HIRADC) method. The results of this study are the factors that cause work accidents in the mold-changing process at the Inject stretch blow machine (ISBM). The stages carried out in this study are hazard identification, risk assessment, risk control, and residual risk assessment. The results obtained from this research are in the form of designing SOP (Standard Operating Procedure) for production activities and installing warnings on each machine, which will be used as a proposal for appropriate work risk control to prevent work accidents in this company. In addition, personal protective equipment that workers can use is the use of gloves, head protectors, and the use of safety shoes. In addition, workers are always required to check the working tools’ condition before starting work. This will be used as an appropriate work risk control proposal to prevent work accidents in this company. In addition, personal protective equipment that workers can use is the use of gloves, head protectors, and the use of safety shoes. In addition, workers are always required to check the working tools’ condition before starting work. This will be used as an appropriate work risk control proposal to prevent work accidents in this company. In addition, personal protective equipment that workers can use is the use of gloves, head protectors, and the use of safety shoes. In addition, workers are required to always check the working tools’ condition before starting work.